SKILLS OF TEACHER’S QUESTIONING IN ENGLISH CLASSROOM INTERACTION AT SMA NEGERI 1 KUALA - Shaffa Vio Adella Panjaitan; Siti Aisah Ginting; Anggraini Thesisia Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
This study was about skills of teacher’s questioning in English classroom interaction. It was aimed to investigate skills of teacher’s questioning used by the English teacher in classroom interaction. The participant of this research was English teacher of SMA Negeri 1 Kuala. The technique of data collection used was observation, video recording, field note and interview. The research finding showed that there are 9 skills that used by the English teacher i.e. structuring, phrasing, redirecting, distributing, pausing, reacting, prompting and changing the level of cognitive demand. Distributing questions were the most dominantly used by the English teacher with 39%.  Redirecting 21%, reacting 13%, pausing 8%, focusing 7%, structuring 4%, changing the level of cognitive demand 4%, phrasing 3% and prompting 1%. Moreover, there were six reasons why teacher ask question in English classroom interaction, they were stimulate and maintain student’s interest, encourage students to think and focus on the content of the lesson, enable teacher to clarify what student has said, enable teacher to elicit particular structures and vocabulary items, enable teacher to check students’ understanding, and encourage students’ participation in a lesson. Related suggestions are given to the English teacher on how to achieve better questions. The study is beneficial for both teacher and students in English classroom interaction. Keywords: Skills of Teacher’s Questioning, Teacher’s Reasons, Classroom Interaction.